As práticas fotográficas de arte como mediação crítica com o espaço construído: a emergência do ordinário e os procedimentos ficcionais - Gabriel de Sousa Castro (2017)
This is an investigation about the potentiality of images as critical mediation with the built space that presupposes two aspects: the visibilities that are displayed by images and the ways the subjects are presented, impacting upon the individuals perceptions. The ordinary is considered a crucial component because the daily spaces are mainly constituted by banality and are recurrently rendered invisible by the familiarity and hegemonic sensibility that reaffirm the most iconic and worthy cities aspects. Arts photographic practices are the object of analysis to discuss and ascertain this qualified mediation, posing several questions about the built environment, the urban artifacts, the city's landscape and its surroundings. The works were organized by identifying certain procedures that are related to a documental approach and to fictional strategies